Pengembangan E-LKPD Berbasis Deep Learning pada Pembelajaran Fisika untuk Meningkatkan Keterampilan Berpikir Kritis dan Berpikir Kreatif Peserta Didik SMA - Linda Khoiro; Yohandri; Fatni Mufit; Emiliannur (Postgraduate, University of Mataram, 2026)
The low critical and creative thinking skills of eleventh grade students at SMAN 1 Lembah Melintang on mechanical wave material, reaching only 38.20% and 47.10% respectively, indicate an urgent need for innovative teaching materials. This study aims to develop a Deep Learning-based Electronic Student Worksheet (E-LKPD) assisted by Heyzine on Mechanical Wave material to improve critical and creative thinking skills of high school students. The research used Research and Development (R&D) method with the Plomp model encompassing three phases: preliminary research, prototyping phase, and assessment phase. The E-LKPD integrates three pillars of Deep Learning: Meaningful Learning, Joyful Learning, and Mindful Learning. The results show that the developed E-LKPD: (1) was declared very valid with an average Aiken V value of 0.87; (2) was declared very practical with a score of 88.54% according to teachers and 84.32% according to students; and (3) proved very effective in improving critical thinking skills from 38.20% to 80.93% and creative thinking from 47.10% to 81.90%, with N-Gain values of 0.691 (medium) and 0.658 (medium) respectively. This Deep Learning-based E-LKPD is suitable as an innovative alternative teaching material in high school physics learning aligned with the demands of the Merdeka Curriculum.